Balinese diglossia shown by public signs as language vitality symbol from linguistic landscape perspective - Widiatmika, Putu Wahyu; Suastra, I Made; Malini, Ni Luh Nyoman Seri (Politeknik Negeri Bali, 2023)
This study is aimed to identify and analyze Balinese diglossia from the perspective of linguistic landscape. Balinese language used in public signs consists of two variations, namely alus and andap. The use of the two variations resembles the culture of Balinese people. Therefore, this study is also intended to provide a new way to view Balinese culture from seeing the Balinese language through non-interactive public signs because there are patterns on each variation used. Furthermore, the use of Balinese variations on signs can be a measurement to acknowledge its vitality; thus, this study is also aimed to measure Balinese language vitality in general and the vitality of its variations. The data of this study were 12 signs collected from banners, billboards, and information signs found in Bali through observation and documentation method. The data were analyzed by using referential identity method with a descriptive-qualitative approach. This study combined the theories of diglossia, context of situation, function of linguistic landscape, Balinese speech levels, and UNESCO vitality level. The result shows that Balinese language signs in public space are able to characterize the diglossia situation of the Balinese people by indicating four features, namely sign makers, participants receiving messages, caste and social status, and domains. The diglossic situation of the Balinese language is indicated by the variation of the Balinese alus, which is the high variety, and the Balinese andap, which is the low variety. The level of language vitality of Balinese high and low is 4, whereas in general is 5.